Work life balance among Chinese employees: pre, during and post Covid 19 - Zizhao, Wang (2022)
Work life balance has become Human Resource Management mantra especially since the outbreak of covid 19 in early 2020. Employees around the global are affected either positively or negatively as a result of their employers’ strategic move to sustain their business while trying to help their employees to maintain work life balance. Similar pattern is observed in China as well where employees from both public and private sectors are affected with some losing their employment while others are trying to balance their work, personal and family life. Given this background, the aim of this study is to examine the correlations between work life balance among Chinese employees both from public and private in different phases i.e. pre, during and post covid 19 and its impact on both return on return on investment (ROI) and return on expectations (ROE). A mixed method was deployed to collect data and in a total of 172 completed questionnaires were collected and supported with 7 semi-structured interviews from human resource managers and employees. The findings from the data analysis indicate that there are differences in terms of work life balance in all 3 different phases and it has significant impact on ROI and ROE. The Chinese culture and values have contributed to the findings where they own the collectivistic nature, individuals in some extent tend to have a lower integration of the family and work spheres compared with western cultures. Relevant recommendations were proposed to all stakeholders with an aim to improve the work life balance among Chinese employees specifically and other employees globally especially in their preparation towards new-norm for post covid 19 era.